THE USE OF CULTURE-BASED TOURIST ATTRACTIONS IN DEVELOPING TOURIST DESTINATION IMAGES A CASE STUDY: NORTH SUMATRA PROVINCE - Sinthon L. Siahaan; Mike Wijaya Saragih (Prodi Sastra Inggris UKI, 2024)
This study examines the use of culture-based tourist attractions in shaping and enhancing the destination image, with North Sumatra Province as a case study. Using a literature review, the study analyzes data from 49 events categorized into nine types, during 2017. The study highlights how cultural attractions, encompassing cognitive, unique, and affective dimensions, contribute to a robust destination image. The knowledge and historical insights offered through these events influence the cognitive image. The unique image arises from the cultural distinctiveness and creative expressions showcased. The affective image, meanwhile, emerges from the emotional connections and memorable experiences visitors encounter. Through cultural festivals, exhibitions, local traditions, and culinary displays, the study identifies effective strategies for leveraging local cultural assets to boost tourism appeal. It underscores the importance of consistent, innovative cultural programming in sustaining and promoting regional identity. The findings point to the role of cultural tourism in fostering destination loyalty and increasing visitor satisfaction.